UJI TOKSISITAS AKUT BIOPESTISIDA PADA Bellamya javanica, v.d Bush 1884 DAN Lymnaea rubiginosa, Michellin 1831 - Agung Willy Pramana, Ida IDewa; Samino, Setijono (Biotropika: Journal of Tropical Biology, 2014)
ABSTRACT Acute toxicity test is one method of pre-clinical trials are used to determine the degree of toxicity of a compound within 24 Hours. Biopesticides are a natural pesticide products made ââfrom plants. The purpose of this study was to determine the acute toxicity value of biopesticides against BellamyÃ¢ javanica, v.d Bush 1884Â and Lymnaea rubiginosa, Michellin 1831 with quantitative measurement using LC50 with a span of 24, 48, 72, and 96 hours. The study was conducted in a laboratory scale with a completely randomized factorial design, using a series of six concentrations and three replicates for each species. LC50 analysis using probit analysis. The results of this study indicate LC50 values ââfor B. javanica, v.d Bush 1884 at observation time 24 hours, 48 hours, 72 hours, and 96 hours is 38.418%, 18.820%, 11.817% and 6.637% and LC50 values ââfor L. rubiginosa, Michellin 1831 at observation time 24 hours, 48 hours, 72 hours, and 96 hours is 6.704%, 4.513%, 3.451%, and 1.307%. Keywords : Biopesticides, Abiotic factors, LC50, Â Acute toxicity